Propriedades magnéticas de ferritas do tipo AFe2O4 (A = Co2+, Ni2+, Cu2+ e Zn2+) obtidas pelo método hidrotermal assistido por micro-ondas - Melo, Rosane Saraiva (2014)
Several devices and equipment uses magnetism as base for its operation. Unfortunately such materials are generally based alloys of transition metals and rare earths that often have high manufacturing costs. Therefore, ferrite based material hás been suggested as an alternative for the current magnetic products due to its high permeability, high electrical resistivity, low eddy current losses, among others, which are influenced by the method of production. Therefore, this work aims to synthesize Cobalt, Nickel, Copper and Zinc ferrites by means of Hydrothermal Method Assisted by Microwave. Besides, all obtained samples were characterized by Fourier transform infrared (FTIR) and Raman spectroscopies, X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Wavelength Dispersive X-ray Fluorescence (WDXRF), Energy-dispersive X-ray spectroscopy (EDS) Vibrating sample magnetometer (VSM). All FTIR spectra have shown divalent metal ions occupancy (tetrahedral sites) at about 590-600 cmˉ¹, whereas the octahedral cations are detected around 400 cmˉ¹. For Raman, 660-720 cmˉ¹ bands are assigned to tetrahedral sites in the ferrite, while in the region of 460-640 cmˉ¹ refer to the octahedral sites in the structure. The XRD results confirmed the formation of single phase spinel cubic arrangement for Co, Ni and Zn and tetragonal arrangement for Cu ferrite. In ferrites Cu and Zn secondary phases CuO and ZnO were found. The average particle diameters are in the micrometer range, EDS and XRF showed stoichiometric amounts of ferrites very close to the theoretical values. Ferromagnetic behaviors were observed for the Cobalt ferrite (Ms - 73.40, Mr - 32.12, Hc - 577.55), Nickel (Ms - 39.20, Mr - 10.91, Hc - 143.58) and Copper (Ms - 23.68, Mr - 14.30, Hc - 327.39), and antiferromagnetic for Zinc ferrite (Mr - 0.007, Hc - 81.46).